If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 39 + -2x = 16x + 15 Reorder the terms: 39 + -2x = 15 + 16x Solving 39 + -2x = 15 + 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. 39 + -2x + -16x = 15 + 16x + -16x Combine like terms: -2x + -16x = -18x 39 + -18x = 15 + 16x + -16x Combine like terms: 16x + -16x = 0 39 + -18x = 15 + 0 39 + -18x = 15 Add '-39' to each side of the equation. 39 + -39 + -18x = 15 + -39 Combine like terms: 39 + -39 = 0 0 + -18x = 15 + -39 -18x = 15 + -39 Combine like terms: 15 + -39 = -24 -18x = -24 Divide each side by '-18'. x = 1.333333333 Simplifying x = 1.333333333
| 8m*2-2m=7 | | 5-8x=50-29x | | 2x^3-2x^2y-84xy^2= | | x^2-12x+15=0 | | -17j-j=16 | | x*2+7x+4=0 | | -11-7x=8x+19 | | -6u-13u=-14 | | 2x^3-2x^2y-24x^2y= | | 11n*2-9n=1 | | -13s+-7s-7s+-15=12 | | 10x^2+19x-15=o | | 2*y=5y*2-3 | | 2x^2-27x=0 | | -2(t+8)+12=-6 | | a-8=25 | | -2 ( t+ 8)+ 12= -6 | | 485-a=79 | | x*2-6*x+9=0 | | Y-0.07=-2.09 | | -8x+8y=8 | | 5u+1=6 | | 12x+11y=624 | | 7x-3=2x+9 | | y=50-5x | | c-2=3 | | 3n-9=-33 | | 6-z=25+2 | | Y=1100+Y | | 625a+25b+c=35 | | 100=50t | | 3m+(m+5)= |